2017
DOI: 10.1371/journal.pone.0176997
|View full text |Cite
|
Sign up to set email alerts
|

Mild and repetitive very mild axonal stretch injury triggers cystoskeletal mislocalization and growth cone collapse

Abstract: Diffuse axonal injury is a hallmark pathological consequence of non-penetrative traumatic brain injury (TBI) and yet the axonal responses to stretch injury are not fully understood at the cellular level. Here, we investigated the effects of mild (5%), very mild (0.5%) and repetitive very mild (2×0.5%) axonal stretch injury on primary cortical neurons using a recently developed compartmentalized in vitro model. We found that very mild and mild levels of stretch injury resulted in the formation of smaller growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Loss of axonal microtubule was found after stretch injury and progressive disassembly of microtubules along the breakage points [35]. Stabilization of microtubule resulted in a significant reduction in the number of fragmented axons following injury [34]. Consistent with previous reports [36], our studies also revealed depolymerization of microtubules.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Loss of axonal microtubule was found after stretch injury and progressive disassembly of microtubules along the breakage points [35]. Stabilization of microtubule resulted in a significant reduction in the number of fragmented axons following injury [34]. Consistent with previous reports [36], our studies also revealed depolymerization of microtubules.…”
Section: Discussionsupporting
confidence: 89%
“…Diffuse axonal injury is a hallmark pathological consequence of non-penetrative mTBI [34]. In neuronal culture model, very mild stretch injury to a localized region of the cortical axon is able to trigger a degenerative response characterized by growth cone collapse and significant abnormal cytoskeleton rearrangement, resulting in the formation of smaller growth cones at the tips of axons and a significantly higher number of collapsed structures at both 24 h and 72 h post injury [34]. Axonal degeneration following stretch injury involves destabilization of the microtubule cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In organotypic cerebellar slices, a biaxial strain of 30% increases axonal amyloid precursor protein accumulation, which supports disrupted axonal transport, and the formation of axonal swellings is observed (Chierto et al., 2019). Of note, the microtubule‐stabilizing drug epothilone D is capable of reducing axon fragmentation after stretch injury in cortical neurons (Yap et al., 2017). In addition to disrupting axonal physiology, axon stretch injury can cause the formation of periodic swellings in dendrites, which could also be the consequence of microtubule rupture and impaired axonal transport (Monnerie et al., 2010).…”
Section: What Can We Learn From Axon Stretch Injury?mentioning
confidence: 99%
“…Furthermore, these abnormalities in cytoskeletal structure could be decreased through the application of the potentially clinically therapeutic microtubule stabilizing agent, Epothilone D (Brunden et al, 2012). While these results exemplify the utility of their device for studying neuronal responses to discrete axonal stretch injury, their device lacked optical transparency for high resolution live time-lapse analysis and the ability to investigate synaptically connected axons from two different neuronal populations (Yap et al, 2017). The injury pad layer was reversibly sealed to the glass coverslip to allow access to the injured neurons for subsequent transmission electron microscopy (TEM) analysis (Table 2).…”
Section: Physical (Stretch/strain) Injurymentioning
confidence: 99%
“…Conversely, the mild stretch injury led to significant axonal degeneration at both 1 and 3 days following injury (Yap et al, ). Recently, this in vitro model of axonal stretch injury was used to investigate axonal responses to single and repetitive stretch injuries in a fluidically isolated microenvironment (Yap et al, ). The study compared the morphology and cytoskeletal profile of growth cones on the tips of the axons following mild (5% strain), very mild (0.5% strain), and repetitive very mild (2 × 0.5% strain) axonal stretch injury.…”
Section: Physical (Stretch/strain) Injurymentioning
confidence: 99%